Characterization of the complete chloroplast genome of Bletilla formosana (Orchidaceae), a medicinal plant in southwest of China - Aien Tao; Feiya Zhao; Cong-long Xia (Mitochondrial DNA. Part B. Resources, 2020)
Bletilla formosana is a medicinal plant commonly used in the southwest of China. In this study, we sequenced the complete chloroplast (cp) genome sequence of B. formosana to investigate its phylogenetic relationship in the family Orchidaceae. The chloroplast genome of B. formosana was 160,036 bp in length with 37.2% overall GC content, including a large single-copy (LSC) region of 87,636 bp, a small single-copy (SSC) region of 18,792 bp and a pair of inverted repeats (IRs) of 26,804 bp. The cp genome contained 104 genes, including 71 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. The phylogenetic analysis indicated B. formosana was closely related to Bletilla striata.